Cleptoptilia pela ave tesourinha Tachornis squamata (aves, Apodidae) no semiárido brasileiro - Silva, Catharina Cristhina de Oliveira (2015)
The bird Neotropical Palm-Swift, Tachornis squamata (Apodiformes, Apodidae), steals feathers of other bird species by kleptoptily behavior. This particular behavior has been described for this bird species in the Amazon, however aspects of kleptoptily have not yet been investigated in other Neotropical biomes, where Neotropical Palm-Swift can be found. The aim of this study was to quantify the kleptoptily behavior of Neotropical Palm-Swift species in urban and non-urban areas in the Brazilian semi-arid region, Caatinga biome. In urban areas, the data collections were carried out between July 2013 and June 2014 between 06:00-10:00 a.m. and between 14:00- 17:00 p.m., in a total of 225h 45min of sampling effort. In non-urban area, the data collections were carried out between September 2013 and June 2014 between 06:00-10:00 a.m., in a total of 50h 30min of sampling effort. The kleptoptily behavior was quantified through of records the number of kleptoptily events, number event of kleptoptily attempts and the number of events which the Neotropical Palm-swift collected feathers that loosened in a spontaneous way of other birds. Were registered in urban areas, 39 kleptoptily events, 385 events of kleptoptily attempts and 875 events of collected feathers that loosened in a spontaneously way of other birds. Were registered in non-urban area, 25 kleptoptily events and 49 events of kleptoptily attempts. In this area were not registered events of collected feathers that loosened spontaneously of other birds. In urban area, the Neotropical Palm-Swift collected feathers of five species of birds, belonging to four families. In non-urban area, feathers were collected from seven species of birds, distributed in six families. In this study, in urban areas, the Neotropical Palm-Swifts were recorded collecting feathers in two different ways: through kleptoptily and through collected feathers that have broken off spontaneously of other birds. In non-urban area, the Neotropical Palm-Swifts only collected feathers through kleptoptily behavior. The different behavior of Neotropical Palm-Swift in the two study areas can be explained in part by synanthropic behavior of this species